Neuronal Matrix Metalloproteinase-2 Degrades and Inactivates a Neurite-Inhibiting Chondroitin Sulfate Proteoglycan - Zuo, Jian (J Neurosci, 1998)
Chondroitin sulfate proteoglycans (CSPGs) are implicated in the regulation of axonal growth. We previously reported that the neurite-promoting activity of laminin is inhibited by association with a Schwann cell-derived CSPG and that endoneurial laminin may be inhibited by this CSPG as well [Zuo J, Hernandez YJ, Muir D (1998) Chondroitin sulfate proteoglycan with neurite-inhibiting activity is upregulated after peripheral nerve injury. J Neurobiol 34:41–54]. Mechanisms regulating axonal growth were studied by using an in vitro bioassay in which regenerating embryonic dorsal root ganglionic neurons (DRGn) were grown on sections of normal adult nerve. DRGn achieved slow neuritic growth on sections of normal nerve, which was reduced significantly by treatment with metalloproteinase inhibitors. Similar results were obtained on a synthetic substratum composed of laminin and inhibitory CSPG. DRGn expressed the matrix metalloproteinase, MMP-2, which was transported to the growth cone. Recombinant MMP-2 inactivated the neurite-inhibiting CSPG without hindering the neurite-promoting potential of laminin. Similarly, neuritic growth by DRGn cultured on normal nerve sections was increased markedly by first treating the nerve sections with MMP-2. The proteolytic deinhibition by MMP-2 was equivalent to and nonadditive with that achieved by chondroitinase, suggesting that both enzymes inactivated inhibitory CSPG. Additionally, the increases in neuritic growth resulting from treating nerve sections with MMP-2 or chondroitinase were blocked by anti-laminin antibodies. From these results we conclude that MMP-2 provides a mechanism for the deinhibition of laminin in the endoneurial basal lamina and may play an important role in the regeneration of peripheral nerve.